2013
DOI: 10.1371/journal.pone.0063422
|View full text |Cite
|
Sign up to set email alerts
|

Poles Apart: Arctic and Antarctic Octadecabacter strains Share High Genome Plasticity and a New Type of Xanthorhodopsin

Abstract: The genus Octadecabacter is a member of the ubiquitous marine Roseobacter clade. The two described species of this genus, Octadecabacter arcticus and Octadecabacter antarcticus, are psychrophilic and display a bipolar distribution. Here we provide the manually annotated and finished genome sequences of the type strains O. arcticus 238 and O. antarcticus 307, isolated from sea ice of the Arctic and Antarctic, respectively. Both genomes exhibit a high genome plasticity caused by an unusually high density and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 106 publications
5
111
0
Order By: Relevance
“…Environmental metagenomics and whole genome sequencing of bacterial isolates have shown that light-induced outward H + pumping rhodopsins, such as BR, PR, and XLR, are abundant and widely distributed in surface-dwelling aquatic microbes (31)(32)(33)(34). Given their ability to capture energy from sunlight, it is apparent that the lightdriven H + -pumping activity of these rhodopsins is favorable for survival in the photic zone of aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental metagenomics and whole genome sequencing of bacterial isolates have shown that light-induced outward H + pumping rhodopsins, such as BR, PR, and XLR, are abundant and widely distributed in surface-dwelling aquatic microbes (31)(32)(33)(34). Given their ability to capture energy from sunlight, it is apparent that the lightdriven H + -pumping activity of these rhodopsins is favorable for survival in the photic zone of aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, diverse Actinobacteria assemblages have recently been found in Arctic sediment samples (Zhang et al, 2014) and are considered to be underestimated in some marine regions (Ghai et al, 2013). Xanthorhodopsins can contribute to microbial rhodopsin diversity in sea-ice (Vollmers et al, 2013), and may have been present, but would not be detected with our PR primers. In general, the relative abundance of the different major groups should be treated with caution.…”
Section: Winter Patterns In Pr Diversitymentioning
confidence: 91%
“…In the acI SAGs, the four enzymes that lead from farnesyl pyrophosphate, the ubiquitous sterol precursor, to b-carotene, the bicyclic conjugated chromophore, (Martinez et al, 2007) are most commonly encoded in a cluster. The final pathway enzyme, a b-carotene cleaving oxygenase, was somewhat surprisingly sequenced only in two of the 11 SAGs, and not co-located with the rhodopsin gene as it is in many marine proteobacteria (Martinez et al, 2007;Riedel et al, 2013;Vollmers et al, 2013). However, one of these SAGs places the oxygenase near a b-carotene pathway gene, likely indicating that it once composed part of a full pathway operon.…”
Section: Ecogenomics Of the Aci Lineagementioning
confidence: 99%